Entrustable professional activities framework for assessment of patient handoffs in dentistry. Issue 1 (23rd September 2021) - Ramaswamy, Vidya; Munz, Stephanie M.; Nalliah, Romesh; Fitzgerald, Mark; Dragan, Irina F.; Karimbux, Nadeem; Shin, Katherine; Danciu, Theodora E.
Abstract: Purpose/Objectives: The aim of this study is to report data on the lack of a proper patient handoff system in dentistry and dental education and to present a possible solution to integrate this into curriculum using the "entrustable professional activities" (EPAs) framework. Methods: Delphi participants from seven US dental schools provided feedback on a preliminary definition of handoff, a mnemonic and an assessment rubric. 2019 American Dental Education Association Commission on Change and Innovation in Dental Education (ADEA CCI) participants further evaluated the handoff EPA using the EQual rubric for EPA quality and structure. Results: Delphi participants identified points of transition in dentistry, selected the D‐PASS as a mnemonic, and agreed with the evaluation rubric. The ADEA CCI participants agreed the handoff EPA describes work that is essential for the profession and suitable for entrustment. Conclusion: The D‐PASS rubric is an effective way to assess patient handoffs.